Breakthrough management principles, skills, and patterns for transformational leadership - Shiba, Shoji; Walden, David (New Delhi Confederation Indian Industry, 2006)
Today need for breakthrough often arises because of business globalization. This book describes principles, skills, and patterns for transformational leadership. The book also includes examples of companies that are struggling with and dealing with the effects of globalization. The book is for English-language readers not only in North America and western Europe but in all countries where there is rapid business change and development, as in Eastern Europe and Asia. We have included case studies from countries in Asia, Europe, and North America. Our target readers are people in companies that are trying to move into new business areas for whatever reason or that must compete on a large geographic scale -- nationally or internationally. Most specifically, we are writing for official leaders of companies as well as for change leaders within companies or other organizations who are trying for change and/or have the freedom to change. The methods we describe apply to all types of activities -- product or service, nonprofit or for-profit, charitable, religious, manufacturing, health care, and so forth.
Keywords: Organizational change; Strategic planning